2014
DOI: 10.1177/1368430214536064
|View full text |Cite
|
Sign up to set email alerts
|

Denying humanness to victims: How gang members justify violent behavior

Abstract: The high prevalence of violent offending amongst gang-involved youth has been established in the literature. Yet the underlying psychological mechanisms that enable youth to engage in such acts of violence remain unclear. One hundred eighty-nine young people were recruited from areas in London, UK, known for their gang activity. We found that gang members, in comparison to nongang youth, described the groups they belong to as having recognized leaders, specific rules and codes, initiation rituals, and special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 62 publications
4
45
1
1
Order By: Relevance
“…Self-identification has been lauded as a reliable method to operationalize gang membership (see Esbensen, Winfree, He, & Taylor, 2001), although it is not without its limits (e.g., Melde, 2016). In this way, our operationalization of criminal groups departs from previous research in that we are unable to validate the full extent to which members self-identify as part of the specific group, or whether the groups in our sample capture symbolic in-group/out-group boundaries seen as particularly important for gang dynamics (Alleyne, Fernandes, & Pritchard, 2014;Hennigan and Spanovic, 2015).…”
Section: Delineating Criminal Group Boundariesmentioning
confidence: 70%
“…Self-identification has been lauded as a reliable method to operationalize gang membership (see Esbensen, Winfree, He, & Taylor, 2001), although it is not without its limits (e.g., Melde, 2016). In this way, our operationalization of criminal groups departs from previous research in that we are unable to validate the full extent to which members self-identify as part of the specific group, or whether the groups in our sample capture symbolic in-group/out-group boundaries seen as particularly important for gang dynamics (Alleyne, Fernandes, & Pritchard, 2014;Hennigan and Spanovic, 2015).…”
Section: Delineating Criminal Group Boundariesmentioning
confidence: 70%
“…Of the 16 studies included within the review, 10 investigated the association of demography with knife crime (table 2). All four studies investigating age found a positive association between knife crime and adolescence (21,26,30,32) . compared to other age groups, is positively associated with being in a gang (23,26,33) .…”
Section: Demographymentioning
confidence: 99%
“…Neutralizations for violence, for example, can alleviate dissonance that results from participating in violent behaviors as part of the gang. In fact, gang youth, when compared to nongang youth, report greater agreement with neutralization techniques (Alleyne, Fernandes, and Pritchard 2014;Alleyne and Wood 2010;Esbensen et al 2010;Esbensen and Weerman 2005;Esbensen 2011, 2014;Peterson and Morgan 2014). Additionally, Bandura (2002) stated that moral disengagement can impact other aspects of individual cognition and affect, arguing that individuals with high levels of moral disengagement are less prosocial, in general, and experience lower levels of guilt.…”
Section: Social Cognitive Theory and Gang Membershipmentioning
confidence: 99%
“…In addition, we make use of social cognitive theory (SCT) to parse out differences across group membership in not only offending, but also individual-level attitudes and values. The use of psychological perspectives to explain gang phenomena has been limited and mostly relies upon attempts to explain in-and outgroup differences (Alleyne, Fernandes, and Pritchard 2014). Gang researchers have called for more research into this arena stating that it would provide a more complete understanding of gangs and gang members (see Wood 2012).…”
Section: Introductionmentioning
confidence: 99%